Factors affecting Bangladeshi private university students’ choice of institutions for undergraduate study / Rumana Liza Anam - Anam, Rumana Liza (Universiti Teknologi MARA, 2019)
In a highly populated country like Bangladesh where standards of living are rising steadily, more and more students are pursuing studies at university level. With only a few publicly funded universities, private universities are now the main avenue for pursuing undergraduate studies. Competition is growing among these universities operating in a heavily regulated sector. Substantial amounts are often being spent on attracting potential students. However, without proper research into the area and understanding how students choose their universities, resources may end up being used ineffectively. This conceptual paper aims to identify the factors that students consider when choosing their universities.